Multifunctional POSS‐Based Nano‐Photo‐Initiator for Overcoming the Oxygen Inhibition of Photo‐Polymerization and for Creating Self‐Wrinkled Patterns. Issue 9 (12th November 2014) - Hou, Honghao; Gan, Yanchang; Yin, Jie; Jiang, Xuesong
<x xml:space="preserve">Abstract</x> Oxygen inhibition remains a challenge in photo‐curing technology despite the expenditure of considerable effort in developing a convenient, efficient, and low‐cost prevention method. Here, a novel strategy to prevent oxygen inhibition is presented; it is based on the self‐assembly of multifunctional nano‐photo‐initiators (F2‐POSS‐(SH)4‐TX/EDB) at the interface of air and the liquid monomer. These nano‐photo‐initiators consist of a thiol‐containing polyhedral oligomeric silsesquioxane (POSS) skeleton onto which fluorocarbon chains and thioxanthone and dimethylaminobenzoate (TX/EDB) photo‐initiator moieties are grafted. Real‐time Fourier‐transform infrared spectroscopy (FT‐IR) is used to investigate the photo‐polymerization of various acrylate monomers that are initiated by F2‐POSS‐(SH)4‐TX/EDB and its model analogues in air and in N2. FT‐IR results show that F2‐POSS‐(SH)4‐TX/EDB decreases the effects of oxygen inhibition. X‐ray photo‐electron spectroscopy and atomic force microscopy reveal that the self‐assembly of F2‐POSS‐(SH)4‐TX/EDB at the air/(liquid monomer) interface forms a cross‐linked top layer via thiol–ene polymerization; this layer acts as a physical barrier against the diffusion of oxygen from the surface into the bulk layer. A mismatch in the shrinkage between the top and bulk layers arise as a result of the different types of photo‐cross‐linking reactions. Subsequently, the surface develops a wrinkled pattern with a low surface energy. This strategy exhibits considerable potential for preventing oxygen inhibition, and the wrinkled pattern may prove very useful in photo‐curing technology.